Factors influencing investment decisions: a study of individual investors in the Indian stock market - Mathew, R.L.; Kumar, S. R. (International Journal of Accounting & Business Finance, 2022)
The increased competition and enormously complex products in the financial services industry make potential investors perplexed as to how to handle the choices they need to make. The quality of the choices made by investors is shaped by a multitude of factors. Nowadays, researchers in the field of finance have already been paying attention to issues impacting individual investors’ investing preferences. The current research being conducted in the Indian stock market intends to better understand the factors that influence the investing decisions of individual investors. This study is designed to investigate the factors that are affecting the stock preferences of individual investors and also seeks to ascertain the relevant factors influencing their investment decisions. An attempt is also made to know the effect of these on their socio-economic variables in the context of the Indian stock market. In addition to the analysis of ranking data, an independent t-test, Analysis of Variance (ANOVA) and relevant post hoc tests were conducted to meet the objectives of the study. The results of primary data analysis indicate that return, risk, and past performance of stocks are the three major factors considered by individual investors while making investment decisions. The present study contributes to the academic community’s interest in the micro area of behavioural finance dealing with the mind and motivations of individual investors, especially in the context of emerging markets. At the same time, the inferences drawn from the present study can be used by future researchers to understand the current preferences of individual investors on factors influencing stock investment decisions.
Keywords: Investor Preferences; Socio-Economic Factors; Investment Decision; Choice Criteria